Analyzing and contrasting the strength of male windsurfers between 2004 and 2006 - Zheng, W.; Ma, Y. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: Several parameters of the physical strength profile of the Chinese Windsurfing team in 2004, 2005 and 2006 were comprehensively compared and analyzed. The physical fitness of the windsurfers was gained to provide guidance for the strategic plan of the Chinese national windsurfing team. Methods The strength of four windsurfers was evaluated in January each year by using the maximum power method of analysis. Results / Discussion To demonstrate the changes in strength over the 3 year period the testing results of one windsurfer were analyzed. It was shown that when the testing weight increased, the average pull-up power and velocity increased. The ratio amplitude of the draw-weight was also the greatest among the parameters. This finding indicated the pull of the windsurfers could increase at the same weight by comparing the data in 2004 and 2005. Thus, the whole physical ability in 2005 was enhanced according to that in 2004. It was also demonstrated that when the weight was 40kg and 55kg, the average power decreased, but the average pull-up velocity increased in 2006 and was higher than in 2005. By comparing the data in 2004, 2005 and 2006, the average weight power of male windsurfers decreased from 2004 to 2005. However, this measure increased when the testing weight was small, and changed distinctly when the testing weight was larger in 2005 to 2006. This was likely due to the 10th National games, fo which every team trained assiduously in October 2005. As a result, the windsurfers needed to make adjustments at the completion of the games. Although the windsurfers returned to training, the physical ability was not optimal in January 2006. This indicated that: the power of individual windsurfers was different at the same testing weight; the power did not increase linearly as the testing weight increased; the power was related to the pull-up velocity; and the velocity should be enhanced to increase the power during training. When windsurfers train, the weight should be in the middle and the velocity should be enhanced to increase the training effect of high strength.